Methods and tools of alternative management in project management - Riabokon, Natalia Petrivna (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2015)
In the paper the concept, content and essence of alternative management which is gaining popularity in Ukrainian companies, especially in companies of project type are reviewed. The components of this concept are structured. Basic definitions that determine the direction of technology of alternative management are systematized. Key principles of alternative management are presented. Methodological approaches, the use of alternative management tools in project management are analyzed. The systematization of technologies of project management is submitted from the point of flexibility. The possibilities of using alternative management in project management in companies considering Ukrainian mentality are determined.